DEVELOPING STUDENTS' SPEAKING COMPETENCE IN ENGLISH TEACHING THROUGH THE USE OF ARTIFICIAL INTELLIGENCE (AI) SOFTWARE - Berdiyeva Anora Jonpo'latovna, (TADQIQOTLAR, 2025)
Abstract: Speaking competence is a fundamental aspect of English language learning  that  significantly  influences  students’  academic  and  professional  success. Traditional  teaching  methods  often  do  not  provide  sufficient  opportunities  for interactive speaking practice or personalized feedback. The integration of Artificial Intelligence (AI) in language education offers innovative solutions to these challenges. AI software can enhance students’ speaking abilities by providing real-time feedback, adaptive  learning  paths,  and  interactive  conversational  experiences.  This  article explores the theoretical foundations of speaking competence, reviews the role of AI in English teaching, and discusses practical approaches to effectively incorporate AI tools in the classroom.